PENGUKURAN NILAI RISIKO PORTOFOLIO SAHAM PADA INDEKS LQ45 DI BIDANG TELEKOMUNIKASI MENGUNAKAN METODE KOPULA CLAYTON - Salsabila Syifa Binsanno; Sudarno Sudarno; Di Asih I Maruddani (Jurnal Gaussian, 2023)
The characteristic of copula is non strict on certain distribution assumptions, can explain nonlinier relationship, and easily construct distribution through the marginals that do not need to come from the same distribution family. Copula will be useful for stock data that has price charts fluctuate rapidly and risk will always follow in investing. The relation between risk and copula in this study is to calculate the risk value in the stock portfolio using VaR with the generation of Monte Carlo simulation through Clayton copula on four companies engaged in telecommunications sector, namely EXCL.JK (PT XL Axiata Tbk), TLKM.JK (PT Telekomunikasi Indonesia Tbk), TOWR.JK (PT Sarana Menara Nusantara Tbk), and TBIG.JK (PT Tower Bersama Infrastructure Tbk) for period 2 January 2020 to 31 December 2021. This study resulted that the selected stock portfolios are EXCL and TBIG which had the highest risk value of -0,062741 at 99% confidence level, so when an investor will invest Rp100.000.000,00 the maximum estimated risk is Rp.6.274.100 within one day.